ANALISA KARAKTERISTIK DAN PARTISIPASI PETANI PADA PENGEMBANGAN USAHA TANI PADI ORGANIK (Oryza Sativa, L.)DI KABUPATEN BOYOLALI - Suswadi Suswadi; Sutarno Sutarno (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2017)
This study aims to identify and analyze the characteristics of farmers and the level of participation of farmers in organic farming practices in rice crops. This research is a quantitative research with data collection techniques using questionnaires. The population in the study is 25% of farmers who practice organic farming. The sample selection was done by simple random sampling (30 random sampling). The method of analysis in this study is the Scoring Average Analysis to see the characteristics of farmers and Likert scale analysis to see the level of farmer participation. The result of identification of the characteristics of farmers are: (1) Men more role than women, (2) age of organic farming business over 50 years. (3) Most farmers in Dlingo village have been living for more than 30 years, (4) the main livelihood of farmers is agriculture, (5) most of the income of certified organic farmers in Dlingo Village is still above Rp. 5.500.000, - (6) ownership of land, that organic farmland is largely self-owned. The result of partipasi analysis shows that the participation of farmers community found in farmer group Pangudi Boga Dlingo Village, Teras Subdistrict, Boyolali District on planning, implementation, implementation and evaluation on organic farming program mostly high farmer participation. Â